"Effect of Palatal Metal Collar's Height on Fracture Resistance of Single Metal-Ceramic Crowns". (7th October 2022) - Aburaisi, Nour; Elbishari, Haitham
Abstract : Objectives . The purpose of this study is to evaluate the effect of the palatal metal collar height on the fracture resistance of metal-ceramic crowns. Materials and Methods . A maxillary premolar typodont tooth was prepared and scanned to fabricate 48 metal analogs. The analogs were then scanned to fabricate metal copings divided into 4 groups according to palatal metal collar height as follows; (C0): 0 mm, (C1): 1.0 mm, (C2): 1.5 mm, and (C3): 2.0 mm. After a standard application of pressed ceramic, each crown was cemented onto its corresponding metal tooth analog. The crown-analog assembly was subjected to a sequence of thermal stressing for 5, 000 cycles. A universal testing machine applied controlled loads to the crowns until fracture. Examination under a stereomicroscope determined the failure mode. A scanning electron microscope (SEM) was used to examine fracture. Load to failure data was analyzed using ANOVA followed by Tukey HSD (P ≤ 0.05 ). Results . ANOVA statistics revealed that groups with a palatal metal collar presented significantly higher failure loads when compared to the collarless group (P < 0.0001 ). Difference in failure loads between 1.5-mm and 2.0-mm palatal metal collar height were not statistically significant (P = 0.935 ). There were no significant differences detected among the groups in terms of failure mode. Conclusions . The height of the palatal metal collar has an effect on the fracture resistance of the metal-ceramic crowns. Clinical Relevance . The incorporation of a palatal collar with a predetermined height is essential to reduce the mechanical failure of metal-ceramic crowns.